(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Massive growth of the Internet has brought in many good things such as e-commerce, easy access to extensive sources of learning material, collaborative computing, e-mail, and new avenues for enlightenment and information distribution to name a few. Today, since almost all the work is done over the internet, crucial data is sent over the web and other information is placed over the internet. So ensuring data security over the internet is very important and should be taken care of at utmost priority. As with most technological advances, there is also a dark side attached to it, i.e. hacking. Hacking is an activity in which a person (namely hackers) exploits the weaknesses and vulnerabilities in a system for self profit or gratification. With the growing movement of the world from offline to online culture like shopping, banking, sharing information access to sensitive information through the web applications has increased. Thus the need of protecting the systems from hacking arises to promote the persons who will punch back the illegal attacks on the computer systems and will ensure data security. As every coin has two faces, this coin also has one another face which generally acts as a life saver for the victims of hacking. This lifeguard technique is called ethical hacking. Ethical hacking is a technique which is used to identify the weaknesses and vulnerabilities in the system or computer network in order to strengthen the system further to prevent the data. The main reason behind studying ethical hacking is to evaluate target system security. This paper helps to generate a brief idea of ethical hacking and all aspects.